Destruction of predators in the ecosystem and its impact on incidence of dengue - Nawab, Kamaruzaman Khan (2017)
Dengue disease in Malaysia is increasing at an alarming rate. The district of Petaling, Selangor contribute more than 50 percent of the total number of Dengue cases in Malaysia. This study was carried out to show the use of Insecticide in Aedes mosquito control is ineffective because they also kill the mosquito predators which deter the breeding of aedes mosquito. It was done by inspecting 85 existing potential breeding points of aedes larvae distributed in 15 localities at hotspots area (where the incidences of dengue outbreak never stop for more than 30 days) with the presence of at least one mosquito predators. Frequency of Aedes larvae breeding, the incidences of dengue in relation to the presence of mosquito predator and the impact of insecticide used in the ecosystem were used to determine the objective. The mosquito predators identified was Gambushia fish, tadpoles, dragonfly nymph, frog and dragonfly. To determine the frequency of mosquito larvae in relation to the presence of predators, inspection was done at 85 existing potential breeding receptacles at 15 localities hotspots daily for 6 month. The use of data from VEKPRO programme under the Ministry of Health Malaysia was accessed to evaluate the amount of insecticide used monthly and in comparative to the number of dengue cases in that area for the year 2014 to 2015. Result: The frequency of larvae breeding and incidence of dengue cases decrease with the presence of mosquito predators. The use of insecticide is directly proportional to the incidence of dengue cases. In conclusion mosquito predators are very vital in controlling the breeding of aedes mosquito but the use of insecticide exterminated and damaged the mosquito predators and their habitat. It is recommended that the use of insecticide in controlling dengue at urban area should be stopped and biological methods to be introduced in curbing dengue.